Association Between Neutrophil to Lymphocyte Ratio and Left Ventricle Global Longitudinal Strain in Acute Myocardial Infarction - Alfa Alfin Nursidiq; Niniek Purwaningtyas; Trisulo Wasyanto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Background: High neutrophil to lymphocyte ratio (NLR) is independently associated with lower EF, in hospital complications, and higher mortality rates in acute myocardial infarction (AMI). Global longitudinal strain (GLS) measurement after AMI demonstrated specific benefit compared with LVEF in evaluation of the extent of post MI left ventricular myocardial injury. The aim of this study was to determine the association between NLR and left ventricular GLS in AMI patients.Methods: An analytic observational study was conducted on August-December 2017 to patients who admited to Dr. Moewardi General Hospital which diagnosed STEMI or NSTEMI. Blood examination and transthoracic echocardiography were performed. They were divided into two groups according to GLS measurement result, GLS>-13.8% and GLS≤-13.8%. The cut-off value of NLR to predict GLS>-13.8%was determined by ROC curve analysis. Bivariate and multivariate analysis to assess whether high NLR was associated with GLS>-13.8% were performed.Results: As many as 57 patients were included in this study, 24 patients (mean age 56,21±9,43) in GLS ≤-13.8% group and 33 patients (mean age 56.67±8.24) in GLS >-13.8%. NLR was significantly higher in GLS>-13.8% group 6.06 (5.36-6.86) compare 4.20 (3.49-5.04),in GLS≤-13.8%, p=0.001. The cut-off value of NLR was 4.69. The bivariate analysis showed that NLR>4.69 associated with GLS>-13.8%, OR 2.70 (CI 95% 1.41-5.17, p=0.001). Multivariate analysis shown that higher NLR have more probability to develop GLS>-13.8%, OR 8.53 (CI 95% 2.38-30.60, p<0.001).Conclusion: There is an association between NLR and left ventricular GLS in AMI patients. AMI patients with high NLR are more likely to have worse GLS.